Imaging in children with ataxia-telangiectasia-The radiologist's approach - Katarzyna Jończyk-Potoczna; Jakub Potoczny; Aleksandra Szczawińska-Popłonyk (Frontiers Media S.A., 2022)
Ataxia-telangiectasia (A-T) is a syndromic inborn error of immunity (IEI) characterized by genomic instability, defective reparation of the DNA double-strand breaks, and hypersensitivity to ionizing radiation disturbing cellular homeostasis. The role of imaging diagnostics and the conscious choice of safe and advantageous imaging technique, as well as its correct interpretation, are crucial in the diagnostic process and monitoring of children with A-T. This study aimed at defining the role of a radiologist in the early diagnosis of A-T, as well as in detecting and tracking disease complications associated with infections, inflammation, lymphoproliferation, organ-specific immunopathology, and malignancy. Based on our single-center experience, retrospective analysis of investigations using ionizing radiation-free techniques, ultrasound (US), and Magnetic Resonance Imaging (MRI), was performed on regularly followed-up 11 pediatric A-T patients, 6 girls and 5 boys, aged from 2 to 18 years, with the longest period of observation coming to over 13 years. Our attention was especially drawn to the abnormalities that were observed in the US and MRI examinations of the lungs, abdominal cavity, and lymph nodes. The abdominal US showed no abnormalities in organ dimensions or echostructure in 4 out of 11 children studied, yet in the other 7, during follow-up examinations, hepato- and/or splenomegaly, mesenteric, visceral, and paraaortic lymphadenopathy were observable. In 2 patients, focal changes in the liver and spleen were shown, and in one patient progressive abdominal lymphadenopathy corresponded with the diagnosis of non-Hodgkin lymphoma (NHL). The lung US revealed multiple subpleural consolidations and B line artifacts related to the interstitial-alveolar syndrome in 5 patients, accompanied by pleural effusion in one of them. The MRI investigation of the lung enabled the detection of lymphatic nodal masses in the mediastinum, with concomitant airway lesions characteristic of bronchiectasis and focal parenchymal consolidations in one A-T patient with chronic respiratory failure. This patient also manifested organomegaly and granulomatous liver disease in abdominal MRI examination. Our study shows that the use of modern US capabilities and MRI is safe and efficient, thereby serving as a recommended advantageous imaging diagnostic tool in monitoring children with IEI and DNA instability syndromes.